Analisis Kemampuan Membaca Lancar Level 3 Siswa Sekolah Dasar Dikota Padang - Mifta Hurrahmi; Wini Media Putri; Chandra Chandra; Ari Suriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The purpose of this study was to compare see students' ability to read fluently at level 3 and to see their ability to explain reading content in terms of students' opinions/perceptions through dialogue texts. This research uses a qualitative approach, with a qualitative descriptive type of research. Data collection techniques in this research consisted of: (1) assessment of level 3 fluent reading abilities (2) interviews with students regarding their perceptions regarding the dialogue texts they read (3) documenting the process of reading the text. . Based on these data collection techniques, the research instruments used consisted of: (1) level 3 fluency reading ability assessment sheet, (2) reading comprehension assessment sheet (3) documentation of students' reading processes. This research was conducted by Mifta Hurrahmi and Wini Media Putri, where the research subjects were elementary school students. The results obtained are based on students' ability to read and explain the contents of the reading from the interviews that have been conducted. It can be concluded that the use of dialogue texts is more effective in determining the level of students' ability to read fluently at level 3 and helping students understand the content of the reading they read